Fe3O4/Mulberry Stem Biochar as a Potential Amendment for Highly Arsenic-Contaminated Paddy Soil Remediation - Ziling Tang; Meina Liang; Yanmei Ding; Chongmin Liu; Qing Zhang; Dunqiu Wang; Xuehong Zhang (Toxics)
Magnetite-loaded biochar has recently received attention owing to its ability to remove arsenic from contaminated soil. In this study, mulberry stem biochar (MBC) and Fe3O4-loaded mulberry stem biochar (Fe3O4@MBC) were produced and used in a 100-day incubation experiment to investigate their performance in the stabilization of arsenic in paddy soil severely polluted by the As (237.68 mg·kg−1) mechanism. Incubation experiments showed that Fe3O4@MBC was more effective in immobilizing As after incubation for 100 days. Moreover, adding Fe3O4@MBC facilitated the transformation of exchangeable heavy metals into organic-bound and residual forms, thereby reducing As available concentrations, mobility, and bioavailability in the soil, and elevating slightly the soil pH and dissolved organic carbon (DOC). The concentration of TCLP-extractable As (AsTCLP) in contaminated soil was reduced from 93.85 to 7.64 μg·L−1 within 10 d, below the safety limit for drinking water set by the World Health Organization (WHO). The characterization results of Fe3O4@MBC after incubation indicated that the mechanisms for As passivation are linked to redox reactions, complexation, electrostatic attraction, surface adsorption, and coprecipitation. Conclusively, Fe3O4@MBC is a promising amendment in highly As-contaminated soil and provides a theoretical reference in such polluted paddy soil remediation.